2020
DOI: 10.3389/fimmu.2020.00491
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Reverses HDAC Inhibitor-Mediated Repression of Aicda and Class-Switching in Antibody and Autoantibody Responses by Downregulation of miR-26a

Abstract: Estrogen contributes to females' strong antibody response to microbial vaccines and proneness to autoimmunity, particularly antibody-mediated systemic autoimmunity, in females. We have hypothesized that this is due to estrogen-mediated potentiation of class switch DNA recombination (CSR) and somatic hypermutation (SHM). As we have shown, estrogen boosts AID expression, which is critical for both CSR and SHM, through upregulation of HoxC4, which together with NF-κB critically mediates Aicda (AID gene) promoter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 119 publications
(221 reference statements)
0
25
0
Order By: Relevance
“…CD19 + GFP + 7-AAD − transduced B cells were sorted by FAC 32 . Expression of Ror α , Tox, Trerf1, Trpv3, and Rassf6 transcripts in B cells transduced with empty or Mir181-expression retroviral construct was analyzed by quantitative RT-PCR 78 , 85 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD19 + GFP + 7-AAD − transduced B cells were sorted by FAC 32 . Expression of Ror α , Tox, Trerf1, Trpv3, and Rassf6 transcripts in B cells transduced with empty or Mir181-expression retroviral construct was analyzed by quantitative RT-PCR 78 , 85 .…”
Section: Methodsmentioning
confidence: 99%
“…The 3′UTRs of TOX , TRERF1, and TRPV3 mRNAs were cloned into the psi-CHECK2 miRNA Expression Reporter Vector System (Promega) downstream of the Firefly luciferase 28 , 85 . TOX , TRERF1, and TRPV3 3′UTR mutant psiCHECK-2 constructs were generated through site-directed mutagenesis of MIR181 target site seed sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Butyrate, which is generated by the fermentation of dietary fiber by intestinal microbiota, is recognized for its therapeutic potential in chronic diseases, including inflammatory bowel disease (IBD), cancer, inherited diseases, and neurological degenerative disorders (22). Butyrate, which functions as a histone deacetylase inhibitor, has also been shown to upregulate B cell microRNAs and modulate antibody and autoantibody responses through its direct effects on B-cellintrinsic epigenetic mechanisms in lupus mouse (10)(11)(12). In addition, butyrate-generating bacteria Lactobacillus fermentum exerted beneficial effects in terms of reducing lupus disease activity and renal damage (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that butyrate can regulate T-independent and T-dependent antibody responses, as well as autoantibody responses, in lupus mouse models by directly influencing B-cell-intrinsic epigenetic mechanisms via the inhibition of histone deacetylases (HDACs) (10)(11)(12). In addition, intervention with a mixture of SCFAs consisting of sodium acetate, propionate, and butyrate decreased proteinuria and inhibited spleen enlargement in lupus-prone TLR7.1 Tg C57B1/6 mice (13).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Casali et al. demonstrated that estrogen counteracts the activity of HDAC inhibitors on the class switching of mouse B cells and the production of autoantibodies ( 114 ). Mechanistically, estrogen reversed the HDAC inhibitor-mediated upregulation of miR26-A, which targets Aicda, the gene that encodes AID ( 114 ).…”
Section: Altered Chromatin Accessibility In Sle B Cellsmentioning
confidence: 99%